2004
DOI: 10.1029/2004gl020212
|View full text |Cite
|
Sign up to set email alerts
|

Disparity of tropospheric and surface temperature trends: New evidence

Abstract: [1] Observations suggest that the earth's surface has been warming relative to the troposphere for the last 25 years; this is not only difficult to explain but also contrary to the results of climate models. We provide new evidence that the disparity is real. Introducing an additional data set, R2 2-meter temperatures, a diagnostic variable related to tropospheric temperature profiles, we find trends derived from it to be in close agreement with satellite measurements of tropospheric temperature. This suggests… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 23 publications
0
14
1
Order By: Relevance
“…On islands with complex terrain, mountains are the dominant factor influencing local temperature. It has been proposed that the lapse rate is spatially variable on a regional scale (Douglass et al , 2004a, 2004b), but this result cannot be confirmed in the present research. Instead, the temperature lapse rate analysed in the present study varies seasonally (Table I; Figure 7).…”
Section: Resultscontrasting
confidence: 87%
“…On islands with complex terrain, mountains are the dominant factor influencing local temperature. It has been proposed that the lapse rate is spatially variable on a regional scale (Douglass et al , 2004a, 2004b), but this result cannot be confirmed in the present research. Instead, the temperature lapse rate analysed in the present study varies seasonally (Table I; Figure 7).…”
Section: Resultscontrasting
confidence: 87%
“…The hiatus sometimes has been only accepted during winter (Cohen et al, 2013), and finally no consensus exists, and Foster and Rahmstorf (2011) and more recently Karl et al (2015) have neglected the hiatus and suggested that the warming rate has remained almost constant until the present. At the same time, temperature evolution has been extensively analysed not only as a consequence of the detection of hiatus (Foster and Rahmstorf, 2011;Hunt, 2011;Kaufmann et al, 2011;Parker, 2011;Cohen et al, 2013;England et al, 2014), but also because satellite observations from 1979 are currently being compared with surface observations (Douglas et al, 2004;Klotzbach et al, 2009), and because regional analyses have detected negative temperature trends, particularly in the United States and China, offering a new and controversial problem in which the quality of data and local factors must be taken into account (Lebassi et al, 2009;Quirk 2012;Capparelli et al, 2013;Misra and Michael, 2013;Peng et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The panel concluded, after considering possible systematic errors that 'substantial disparity remains.' From a study of several independent observational datasets (Douglass et al, 2004b) confirmed that the disparity was real and arose mostly in the tropical zone. Also, Douglass et al (2004a) showed that three state-of-the-art General Circulation Models (GCMs) predicted a temperature trend that increased with altitude, reaching a maximum ratio to the surface trend ('amplification' factor R) as much as 1.5-2.0 at a pressure (altitude) about 200-400 hPa.…”
Section: Resultsmentioning
confidence: 91%
“…The first group would comprise the errors in the measurement procedure; the second group would refer to various impacts of natural and anthropogenic factors on temperature at certain altitudes; and the third group would be base on the divergence in spatial distribution of observations (Santer et al, 2000). However, the divergences are inevitable reality (Douglass et al, 2004b). On the other hand, the analysis of radio sonde data in lower and middle layers of troposphere match the UAHMSU data, which supports the statement on the data reliability (http:// www.marshall.org/pdf/materials/415.pdf).…”
Section: Resultsmentioning
confidence: 99%